PENGARUH PENGGUNAAN ALAT PERAGA AEM (ALGEBRAIC EXPERIENCE MATERIALS) TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA POKOK BAHASAN OPERASI BENTUK ALJABAR - siti jamilah; Reza Oktiana Akbar (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
Mathematicts learning process ussually takes place with the lecture method. So that students just listen, not many ideas put forward, students feel bored, especially math lessons they find difficult. In mathematical operations form the subject of algebra are abstract elements, they have difficulty understanding abstract concepts. One effort to help students understand the concept of algebra by using props AEM (Algebraic Experience Materials). The purpose of this study to determine the students 'response to the use of props AEM (Algebraic Experience Materials), to determine students' creative thinking skills in the subject of mathematics learning operations in the algebra of MTs Al-Hidayah Ciawijapura. In addition, to determine the effect of the use of props AEM (Algebraic Experience Materials) to creative thinking skills of students on the subject of operations in the algebra of MTs Al Hidayah Ciawijapura. Based on the results of the study, students' response to the use of props AEM (Algebraic Experience Materials) in mathematics including a very strong category with an average of 82.23%. Creative thinking skills of students in mathematics learning test average of 75.21%, the value of good category. While the results of the use of the analysis of hypothesis testing showed t_hitung> t_tabel or 2.977> 2.042. This means that the use of props AEM (Algebraic Experience Materials) to creative thinking skills of students there is the influence of 22.29% and the remaining 77.71% influenced by other factors not examined.